Effects of two-week machine massage on muscle properties in adolescent wrestlers - Qu, Guangcai; Wang, Hongbo; Zhou, Guohai; Liu, Haiping (Frontiers in Physiology, 2023)
Objective: This study aimed to investigate the effect of a two-week machine massage on the physical properties of the erector spinae and serum biochemical indexes of adolescent athletes after training. Methods: Sixteen male adolescent wrestlers were recruited (age: 15 ± 1 years; height: 166 ± 7 cm; weight: 56 ± 7 kg) and randomly assigned to machine massage (MA, 8) and control (CO, 8) groups. Participants in the MA group received machine massage for 20 min after each wrestling training from Monday to Saturday (except on Thursday) for two weeks, while the participants in the CO group recovered naturally. Over the course of two weeks, all the participants underwent similar wrestling training program under the guidance of a professional coach. Before and after the intervention, serum urea and creatine kinase (CK) levels were measured in a fasting state. A Myoton Pro digital muscle evaluation system was used to measure the physical properties of the erector spinae, including the oscillation frequency, logarithmic decrement of a muscle`s natural oscillation, and dynamic stiffness. Results: After two weeks of machine massage treatment, the dynamic stiffness of the erector spinae in the MA group decreased by 12.90% and that in the CO group increased by 2.34%, indicating a significant difference between the two groups (P=0.04, ƞ2=0.286). The decrease in the logarithmic decrement of a muscle’s natural oscillation value in the MA was significantly greater than that in the CO (P=0.003, ƞ2=0.286). Moreover, the serum CK values decreased by 33.84% in the MA group and by 1.49% in the CO group, despite a trend of change between the groups (P=0.062, ƞ2=0.084). No significant difference was found in the improvement in serum urea levels between the two groups after two weeks of treatment. Conclusions: Results of the present study indicated that a two-week machine massage had a positive effect on the improvement of the physical properties of the erector spinae of wrestlers during training.